2010
DOI: 10.1002/jsfa.4037
|View full text |Cite
|
Sign up to set email alerts
|

Vascular effects of egg white-derived peptides in resistance arteries from rats. Structure-activity relationships

Abstract: These peptides could reduce the vascular resistance and be used as functional ingredients in the prevention and/or treatment of hypertension and other associated disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…We for the first time report direct relaxant effects of milk protein derived peptides in small distal mesenteric arteries from hypertensive rats, which have a predominant role in the regulation of blood pressure through the control of the systemic vascular resistance. Our findings are in line with relaxant effects of different original or modified egg protein derived peptides in canine mesenteric artery [25], hypertensive rat mesenteric artery [26,27], and small distal branches of rat mesenteric artery [28].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We for the first time report direct relaxant effects of milk protein derived peptides in small distal mesenteric arteries from hypertensive rats, which have a predominant role in the regulation of blood pressure through the control of the systemic vascular resistance. Our findings are in line with relaxant effects of different original or modified egg protein derived peptides in canine mesenteric artery [25], hypertensive rat mesenteric artery [26,27], and small distal branches of rat mesenteric artery [28].…”
Section: Discussionsupporting
confidence: 86%
“…It should be noted that proximal rat and canine mesenteric arteries were used in those studies. Quite interestingly, COX inhibition produced increase instead of reduction of mesenteric artery relaxation induced by different original or modified egg protein derived peptides [25,27,28], thus indicating the involvement of prostanoids with a net relaxant contribution. Therefore, the role of COX products in mesenteric artery relaxation seems to depend on the peptide sequence/source, the proximal or distal artery level and the animal species, as well as on its normotensive or hypertensive state.…”
Section: Discussionmentioning
confidence: 94%
“…Once the peptide passes through the small intestine, it reaches the large intestine. Then, most of the absorption takes place in the half of the colon defined as the “absorbing colon” (Garcia‐Redondo and others ).…”
Section: Absorption Of Ace Inhibitory/antihypertensive Peptidesmentioning
confidence: 99%
“…Several studies have shown beneficial effects of bioactive peptides derived from dietary proteins on endothelial dependent vascular responses. In this sense, we have previously reported endothelium‐dependent vasodilator responses induced by bioactive peptides derived from egg proteins (Garcia‐Redondo, Roque, Miguel, Lopez‐Fandino, & Salaices, ; Miguel et al, ). In addition, several experimental and clinical studies have also found improvement of vasodilator function using bioactive peptides from milk proteins in different conditions (Ballard et al, ; Sipola et al, ).…”
Section: Discussionmentioning
confidence: 93%